Assessing adherence and exploring barriers to provision of prescribed texture modifications for dysphagia in a residential aged care facility in rural Australia. (2nd January 2022) - Hill, C.; Clapham, R. P.; Buccheri, A.; Field, M.; Wong Shee, A.; Alston, L.
Abstract: Purpose: Purpose: Between 55–65% of residents living in residential aged care facilities (RACFs) experience dysphagia and are prescribed texture-modified diets by a speech-language pathologist (SLP). The aim of this study was to assess current adherence to prescribed texture modification for people with dysphagia; and explore barriers to implementation in a rural aged care setting. Method: Method: Meal texture audits ( N = 42) were completed with residents with dysphagia in a rural RACF who were prescribed texture-modified diets or fluids by a SLP. Semi-structured focus groups were conducted with nursing and food preparation staff ( N = 11) to identify barriers to implementation. Result: Result: Mealtime texture audits identified that 54.8% ( n = 23) of residents' food modification requirements were incorrectly documented in the manual entry database (kitchen form) and 64.3% ( n = 27) of meal trays contained foods that did not meet residents' dysphagia management plans. Focus group data revealed seven main themes impacting on the ability of staff to implement prescribed texture-modified diets. Complicated processes and communication between nursing, food services and SLP staff were identified as major barriers. These were complicated further by time pressures experienced by staff as well as staffing issues, resourcing of the kitchen, accommodating individual dietary preferences and the variety/presentation of dietary options at the aged care facility. Conclusion: There was low adherence to SLP prescribed texture-modified diets and fluids in the participating rural RACF. This study identified major barriers to implementing SLP prescribed texture-modified diets including complicated processes, communication breakdowns, time pressures and limited staffing. Implementation of an online menu management system and regular dysphagia-specific training may address barriers to communication and complicated paper-based menu systems and should be a priority for health services to ensure adequate dysphagia management.